2020
DOI: 10.18632/aging.103906
|View full text |Cite|
|
Sign up to set email alerts
|

RNA-seq reveals the diverse effects of substrate stiffness on epidermal ovarian cancer cells

Abstract: Background: Increasing evidence has confirmed that ovarian cancer is a mechanically responsive tumor both in vivo and in vitro . However, an understanding of the complete molecular mechanism involved in the response to substrate stiffness is lacking, as the associated transcriptome-wide effects have not been mapped. This limited understanding has restricted the identification of potential mechanically responsive targets in ovarian cancer. Results: To add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Moreover, Martuszewska et al [ 32 ] suggested that the presence of TNS3 at the cell periphery stabilizes the structure of the cells by limiting their motility, and thus reduces metastatic potential. An RNA-seq analysis revealed a significant involvement of TNS2 in the formation of focal adhesions which are associated with the development of metastases in numerous cancers [ 33 ]. Our findings did not show any relationships between TNS2 and TNS3 expression and metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Martuszewska et al [ 32 ] suggested that the presence of TNS3 at the cell periphery stabilizes the structure of the cells by limiting their motility, and thus reduces metastatic potential. An RNA-seq analysis revealed a significant involvement of TNS2 in the formation of focal adhesions which are associated with the development of metastases in numerous cancers [ 33 ]. Our findings did not show any relationships between TNS2 and TNS3 expression and metastases.…”
Section: Discussionmentioning
confidence: 99%
“…). 4,58 Furthermore, lower TNS2 expression was correlated with poor relapse free survival probabilities in one lung and one breast cancer dataset (Table 2…”
Section: Clinical Correlationmentioning
confidence: 99%